EMBR-19. SHH-DRIVEN MEDULLOBLASTOMA WITH CONCURRENT UNILATERAL RENAL AGENESIS. (1st June 2021) - Aaroe, Ashley; Sarkar, Sanila; Sherani, Farha; McAleer, Mary; Fuller, Greg; Zaky, Wafik
Abstract: Case Presentation: A 3-year-old female with insignificant past medical history presented with 6 weeks of headaches, emesis, and lethargy. MR imaging identified a heterogeneously enhancing right cerebellar hemispheric mass and obstructive hydrocephalus. Gross total resection was performed without complications; pathology revealed classical WHO grade 4 medulloblastoma (MB). MR imaging of the spine and cerebrospinal fluid testing were negative for disseminated disease. Treatment for standard risk medulloblastoma was initiated, comprising proton craniospinal irradiation with posterior fossa boost and concurrent vincristine, followed by adjuvant chemotherapy with vincristine, lomustine, cisplatin, and cyclophosphamide as standard of care. Next generation sequencing of the tumor tissue performed using a high-multiplex PCR-based NGS panel was negative for alteration of the SMO, PTCH1 and CTBNN1 genes. Further molecular characterization via methylation profiling demonstrated the sonic hedgehog (SHH) molecular subtype. Prior to initiation of chemotherapy, renal ultrasound was performed and identified congenitally absent right kidney; audiology evaluation was unremarkable. Discussion: In patients with Gorlin syndrome, cases of unilateral renal agenesis in association with germline SHH-pathway mutations have been reported [1]. SHH signaling is implicated in multiple steps in the development of the urinary system [2]. Outside Gorlin syndrome, however, to the best of our knowledge unilateral renal agenesis coinciding with SHH-driven MB has not been reported. Our patient notably lacks any clinical stigmata of Gorlin syndrome (skeletal abnormalities, skin pits, macrocephaly) and does not exhibit the characteristic germline genetic abnormalities that define GS (PTCH1 mutation or 9q22.3 microdeletion). There are important treatment implications for patients with the constellation of abnormalities we describe here, particularly regarding the requisite frequent monitoring of renal function during multi-agent chemotherapy courses. Our patient tolerated chemoradiation well, and is currently on maintenance chemotherapy with favorable course to date.